Institutionalize Senior Public Management in Argentina in OECD times - Macco, Gonzalo (Revista del CLAD Reforma y Democracia, 2025)
The main objective of this reflection article is to critically analyze the impact of Argentina’s entry into the Organization for Economic Cooperation and Development (OECD) on the consolidation of the senior public management system. Undoubtedly, the modernization of the civil service will be one of the fundamental pillars for its entry, since more than 75 % of the OECD member countries have implemented specific practices for the hiring, evaluation and professional development of their public managers. To this end, it is proposed to reflect on whether corruption and highly institutionalized clientelism in the country are one of the possible limitations for the non-conformation of a professional and independent management space. With the objective of analyzing the impact of clientelism in management positions, this reflection summarizes the various postulates related to the subject, detailing the current situation of the senior public management system in the Argentine Republic, the impact or not of politically made appointments with the corruption perception indices, to reach a conclusion regarding why we understand that it is an opportune moment to begin to install a true process of institutionalization of the professionalized management segment in Argentina. Finally, we briefly explain the way that we consider pertinent for the purposes of being able to install a professional senior public management system in Argentina, adapting to the measures or strategies proposed by Cortázar, Lafuente and Schuster (2014).